2017
DOI: 10.1021/acs.orglett.7b03016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzo[1,4]heterocycles using Palladium Catalyzed Heck Reaction to Vinylogous Carbonates/Carbamates: Unexpected Formation of Indoles via Carbopalladation Intercepted by Nucleopalladation

Abstract: An efficient protocol for the stereoselective synthesis of benzo[1,4]heterocycles via palladium catalyzed Heck reaction on o-halo-aryl-oxa/thia/aza tethered vinylogous carbonates/carbamates/esters has been developed. Unexpected formation of indoles is observed when unprotected 2-iodoaniline tethered vinylogous carbonates are subjected to the Heck reaction. Mechanistic studies indicate that formation of these indoles is an outcome of the interception of the carbopalladation step by nucleopalladation. The method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Finally, the mechanism of the α-arylation step was supported by density functional theory (DFT) calculations. Gharpure studied the Heck reaction for the synthesis of benzo [1,4]heterocycles, and found that iodo aza-tethered vinylogous carbonates led to indoles instead of the expected oxazepines (Scheme 30) [56]. They also proposed the mechanism depicted in Scheme 30, after carrying out some test experiments.…”
Section: Palladiummentioning
confidence: 99%
“…Finally, the mechanism of the α-arylation step was supported by density functional theory (DFT) calculations. Gharpure studied the Heck reaction for the synthesis of benzo [1,4]heterocycles, and found that iodo aza-tethered vinylogous carbonates led to indoles instead of the expected oxazepines (Scheme 30) [56]. They also proposed the mechanism depicted in Scheme 30, after carrying out some test experiments.…”
Section: Palladiummentioning
confidence: 99%
“…The reaction proceeded at 100 °C, and the chemical yields were very high (72−94%, Scheme 51). 79 Mitomycins, a family of bioactive natural products, feature a compact 6/5/5-fused polycyclic ring structure. The first enantioselective synthesis of (+)-mitomycin K was reported using, as key step, an enantioselective oxidative cyclization catalyzed by a palladium/(+)-sparteine system involving two 5exo-trig-cyclizations promoted by two consecutive alkene relay systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9 The Anuradha group reported a protocol for the synthesis of benzoheterocycles [1,4] by using palladium-catalyzed Heck reactions to obtain vinylogous carbonates/carbamates. 10 Although these methods are useful and novel, most are limited by the requirement of metal catalyst and long reaction routes. Indole is another useful heterocyclic compound that is widely distributed in nature.…”
mentioning
confidence: 99%
“…The Basso group reported the synthesis of triazolo-fused benzoxazepines and benzoxazepinones through the Passerini reaction . The Anuradha group reported a protocol for the synthesis of benzoheterocycles [1,4] by using palladium-catalyzed Heck reactions to obtain vinylogous carbonates/carbamates . Although these methods are useful and novel, most are limited by the requirement of metal catalyst and long reaction routes.…”
mentioning
confidence: 99%